2016
DOI: 10.1002/ente.201600131
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing Bending Stresses on Lithium‐Ion Battery Cathodes induced by the Assembly Process

Abstract: The industrialized winding of electrode–separator composites (ESCs; “jelly rolls”) applies bending stress to the winding mandrel. This affects the mechanical integrity of the substrate's coating and adhesion and may reduce the cycle stability and the battery life. Even though this motivates strong interest in the minimization of bending stress during production, there is no testing method available yet to characterize the composite such that process parameters can be derived. This article introduces a test met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 23 publications
1
32
0
Order By: Relevance
“…Studies on the effects of calendering graphite anodes and their processabilities have shown that calendering improves the wetting rate of the anodes due to particle realignment and an increase in divergence within the pore networks, whereas calendering beyond an optimum level reduces wetting rates due to reduction in porosity and average pore diameter . In addition, it was shown that calendering increases the breaking stress of the laminate, simultaneously increasing its brittleness . In another study, it was shown that the calendering of lithium nickel manganese cobalt oxide cathode (NMC) affects their structure by reducing the pore size and eventually cracks the active material particles …”
Section: Introductionmentioning
confidence: 99%
“…Studies on the effects of calendering graphite anodes and their processabilities have shown that calendering improves the wetting rate of the anodes due to particle realignment and an increase in divergence within the pore networks, whereas calendering beyond an optimum level reduces wetting rates due to reduction in porosity and average pore diameter . In addition, it was shown that calendering increases the breaking stress of the laminate, simultaneously increasing its brittleness . In another study, it was shown that the calendering of lithium nickel manganese cobalt oxide cathode (NMC) affects their structure by reducing the pore size and eventually cracks the active material particles …”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it could reduce the cohesive strength and ionic conductance. [ 125,126 ] The achieved coating density and porosity of the electrode after calendering was revealed an exponential correlation with the applied line load, and a mathematical description was developed to qualify the converging course to a density maximum or porosity minimum. [ 127 ] The characteristic parameter, compaction resistance, represents the compaction resistance of the electrode coating, which is identified to be highly dependent on the used materials and formulations and the pore structures developed in the coating, but less dependent on the roller speed.…”
Section: Transforming Materials Into Practicalmentioning
confidence: 99%
“…On the one hand, clean energy is widely used, and traditional energy conversion storage equipment has been unable to satisfy various demands . On the other hand, the widespread use of portable electronic devices, electric vehicles, and the Internet of things leads to people need higher requirements for energy storage devices . Lithium‐ion batteries(LIB) have been widely studied due to their light weight, high energy, and safety .…”
Section: Introductionmentioning
confidence: 99%